Possible contributions of group III/IV muscle afferent feedback to exercise performance - Matsuura, R. (The Journal of Physical Fitness and Sports Medicine, 2016)
Exercise performance cannot be maintained indefinitely, i.e., it deteriorates progressively. Traditionally, deterioration of exercise performance has been attributed to failure of peripheral or central functions of muscle activity. However, muscle rigor (i.e., complete failure of muscle contractile function) never occurs and the muscle force exerted never decreases to zero even with sustained maximal muscle contraction. Furthermore, an increase in central motor output to skeletal limb muscles, and consequently, enhancement of exercise performance, is often observed at the end of a time trial race at which impairment of muscle contractile function is greater. These indicate that only failure of peripheral or central function of muscle activity determines exercise performance. However, recent studies have elucidated that group III/IV muscle afferent inputs to the central nervous system have an important role in the regulation or limitation of exercise performance. This article reviewed two viewpoints regarding contributions of group III/IV muscle afferent feedback to regulation of exercise performance.